Small Business Survival in a Resort Town and Their Views on Location, Marketing, and Challenges of Doing Business (Journal of Organizational Psychology, 2022)
This research was an exploratory survey of small businesses in Breckenridge Colorado to determine how important location was to their businesses, their use of traditional marketing, and their challenges surviving in a resort town. The survey covered a variety of businesses and found that the group of retail, entertainment, and food services was very reliant on tourism and therefore very concerned about their location. This group’s mean reliance on tourism was higher than the sample mean. The results are not surprising, but they do emphasize this group’s focus on location. The results need to be verified with a larger sample size or the use of small sample methods. What was surprising was this group’s use of not just location but a mix of traditional marketing and advertising techniques to gain customer recognition. Also surprising were their comments that survival in a resort town was challenging given internet competition, the difficulty of finding and retaining motivated employees, and the myriad of government regulations they faced.
Keywords: organizational psychology; location; marketing; challenges of running a business; society value of small businesses